ACERCAMIENTO A LA MEDICINA MORTAL DEL NAZISMO - Hernández-Negrín, Halbert; Pérez Valdivia, Arlenys; Padilla Cueto, David; Negrín Jurajuria, Aurora (Revista 16 de abril, 2017)
Any discussion of the events that occurred in Germany during the period between 1933 and 1945, includes a debate about the role that German medicine played in them. A bibliographic review was carried out with the objective of arguing the importance that medicine had for the establishment and development of the Nazi Regime, for which 15 bibliographies were consulted. The Nazi doctors participated in the development and application of methods of mass extermination, being responsible for the murder and sterilization of thousands of people. In the concentration camps they conducted experiments on humans and selected individuals who would die. German medical research and education institutes benefited from the corpses of the deceased. The study of the role of medicine in Nazism can be a means that contributes to the training of health professionals and thus avoid the repetition of these events.